2014
DOI: 10.1021/jp508026g
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Oxidation of Graphene Through Ultraviolet/Ozone Treatment and Its Nonthermal Reduction through Ultraviolet Irradiation

Abstract: We present alternative methods to oxidize a graphene layer through ultraviolet (UV)/ozone (O3)-treatment, resulting in chemically homogeneous graphene oxide (GO), and then to reduce GO through UV-irradiation. Both UV/O3-treatment and UV-irradiation were performed at room temperature in atmospheric pressure for only several minutes and did not involve any wet chemical treatments. The quantity of doped oxygen, determined using X-ray photoelectron spectroscopy, increased after oxidation and decreased after reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 31 publications
(89 reference statements)
4
72
1
Order By: Relevance
“…In our approach, the amount of oxygen atoms generated in graphene can be tuned by controlling the UV/O 3 treatment time in air . It is worth noting that the low oxygen concentration existing in atmosphere is essential for preventing graphene from being over‐oxidized.…”
Section: Methodsmentioning
confidence: 99%
“…In our approach, the amount of oxygen atoms generated in graphene can be tuned by controlling the UV/O 3 treatment time in air . It is worth noting that the low oxygen concentration existing in atmosphere is essential for preventing graphene from being over‐oxidized.…”
Section: Methodsmentioning
confidence: 99%
“…Literatures revealed that ozonation also resulted in changes in surface chemistry of nanocarbons, which would affect their adsorption capabilities. [32][33][34] In order to investigate the changes in adsorption capacity arising from ozonation, rGO-300 was treated in solution by ozone for different time intervals and its adsorption abilities in PHBA were evaluated and compared (Fig. S6).…”
Section: Catalytic Ozonation Employing As-synthesized Go and Rgo Samplesmentioning
confidence: 99%
“…In detail, by introducing CVD growth methods for largescale graphene sheet, instead of the graphite powder we used here, the amount and distribution of the epoxy groups are precisely manipulated. 42,43 Accordingly, it is possible to engineer the magnetism of the GO sheet and consequently employ GO for spintronic device applications. …”
mentioning
confidence: 99%